Comparing the effects of general and spinal anesthesia on the postoperative pain intensity in patients undergoing emergent elective cesarean section - UMUROĞLU, TÜMAY (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: The aim of this study is to compare the effects of general and spinal anesthesia on postoperative pain intensity and analgesic agent requirements in patients scheduled for emergent or elective cesarean sections. Patients and Methods: This was a prospective, observational study conducted in patients who underwent emergent or elective cesarean delivery under spinal or general anesthesia. Postoperative pain intensity and analgesic agent requirements, postoperative complications and patients' satisfactions were evaluated during the first 48 h postoperatively. Results: A total of 212 parturients were enrolled; 104 (53 elective, 51 emergent) patients received general and 108 (54 elective, 54 emergent) patients received spinal anesthesia. Preoperatively, patients who underwent emergent cesarean section under spinal or general anesthesia had higher Numeric Rating Scale (NRS) scores than the patients who underwent elective cesarean delivery (p<0.001). In the first postoperative 48 h, NRS pain scores were similar in patients who underwent emergent or elective cesarean sections under spinal or general anesthesia. Postoperative analgesic agent requirements and patients' satisfactions were not statistically significant between groups. Conclusion: The effects of general and spinal anesthesia on postoperative pain were similar in emergent and elective cesarean sections. Therefore, postoperative analgesic effect should not be a determining factor in choosing the anesthesia method in cesarean sections.
Keywords: Cesarean section; Emergent cesarean sections; Elective cesarean sections; Postoperative pain; General anesthesia; Spinal anesthesia; PREOPERATIVE ANXIETY; DELIVERY PAIN; SATISFACTION